FRI0504 Diffuse alveolar haemorrhagein anca-associated vasculitis: can we predict outcome? an italian multicentre retrospective long-term study of 102 patients. (12th June 2018) - Quartuccio, L.; Bond, M.; Monti, S.; Felicetti, M.; Furini, F.; Murgia, S.; Berti, A.; Emmi, G.; Pazzola, G.; Bozzolo, E.; Leccese, P.; Raffeiner, B.; et al.
Abstract : Background: Diffuse alveolar haemorrhage (DAH) is a rare and severe manifestation of ANCA-associated vasculitides (AAV). Objectives: To identify predictors of survival in patients with AAV-DAH. Methods: A retrospective study of 102 consecutive patients (50% females; mean age 59±17 years) from 27 Italian Centres diagnosed with AAV-DAH was planned. Cox regression unadjusted analyses were performed. Results: Among AAV patients, 47% had Granulomatosis with Polyangiitis (GPA), 47% Microscopic Polyangiitis (MPA) and 6% Eosinophilic Granulomatosis with Polyangiitis (EGPA). At DAH onset, mean BVAS was 20±8 and most patients had renal involvement (RI). Admission to Intensive Care Unit was needed in 27% of patients, while ventilatory support (VS) was required in 46%. At least one cardiovascular risk factor (CVRF) was recorded in 48%. Over a median follow-up of 39 months (25%–75% IQR 66 months), 19/102 patients (18.6%) died (figure 1). All patients received high-dose glucocorticoids in association with Cyclophosphamide (CYC 78%, mean cumulative dose 8±7 g) or Rituximab (37%). Plasma exchange was performed in 46%. Infections occurred in 38%. Age>65 years (HR 3.05 [95% CI 1.18–7.9], p=0.04), CVRF ≥2 (HR 8.85 [95% CI [AG7] 2.34–33.50], p=0.01), BVAS (v.3) (HR 1.07 [95% CI 1.01–1.13], p=0.01) were associated with mortality, whereas FFS was not. The need for VS (HR 4.54 [95% CI 1.48–13.85], p=0.008) and infections (HR 3.98 [95% CI 1.48–10.69] were also associated with mortality. Conclusions: Older age, VS, CVRF and infections affect the survival in AAV. There is a need for specific outcome measeures. Disclosure of Interest: None declared